Red book (Chicago : Red Book Corp., 1903)
"The magazine for young adults" (varies).
Absorbed: American home, with v. 150, no. 5 (Mar. 1978).
Description based on print record.
Latest issue consulted: Vol. 231, no. 4 (Nov./Dec. 2018) (surrogate).
Keywords: Women -- Periodicals; Young women -- Periodicals; Young adults -- Periodicals; Lifestyles -- Periodicals; Young women; Young adults; Lifestyles; Women; Electronic journals